High-throughput screening for target compounds in smokeless powders using online-SPE tandem mass spectrometry. Issue 1 (2nd January 2021) - Taudte, Regina Verena; Roux, Claude; Bishop, David P.; Fouracre, Chris; Beavis, Alison
ABSTRACT: The detection and quantification of compounds present in smokeless powders plays an important role in various fields such as environmental and forensic science. Often, time and labour consuming sample preparation techniques such as solid phase extraction (SPE) are required to facilitate either pre-concentration or sample clean-up with complex matrices. This paper describes the first application of the completely automated online SPE system RapidFire® connected to a triple quadrupole mass spectrometer for smokeless powder/gunshot residue analysis. The optimized method involved sample loading during 2000 ms using UP water (0.1% formic acid) at a flowrate of 1.25 mL/min on a Type C C18 cartridge followed by elution of the target compounds for 3000 ms using IPA (0.1% formic acid) at 0.75 mL/min. Target compounds were detected in soil (DPA, 2-NDPA, EC, NG, 2, 4-DNT) and cotton swabs (NG) in only 8 seconds per sample with detection limits of 0.223 ppm (DPA), 0.104 ppm (2-NDPA), 0.0949 ppm (EC), 0.187 ppm (NG) and 0.128 ppm (2, 4-DNT). The presented method showed promising results for the analysis of five target analytes in soil samples. Further optimisations can extend the analysis to other sample matrices and include more analytes potentially present in smokeless powders and GSR.